Evaluation of demographic characteristics and comorbidities in patients with surgical site infection after gynecological surgeries, 2016-2020 - Farzipour, Shahla; Jalilvand, Faranak; Sharghi, Afshan; Mostafaei-Aghah, Ehsan (International Surgery Journal, 2022)
Background: Surgical site infection (SSI) is one of most common infections in the hospital and complications in patients admitted to the surgical ward or outpatient surgery, which increases the duration of treatment, delays wound healing, increases the use of antibiotics, causes unnecessary pain and in severe cases death and imposes a lot of costs on the health care system. The aim of this study was to determine the demographic characteristics and comorbidities in patients with SSI. Methods: The study population included 92 patients who referred to Alavi hospital in Ardabil for gynecological surgeries from June 2016 to the end of April 2020. Their complete hospital records were extracted through the hospital archive system and carefully studied. A special checklist was filled out for each patient. The information in the checklist included age, occupation, place of residence, marriage, education, type of surgery performed, presence or absence of underlying disease, cancer, smoking and alcohol consumption and presence or absence of a history of abdominal and pelvic surgery. All data analyzed by statistical methods in SPSS. Results: Most of patients with SSI were between 30 to 40, rural, married and housewives. Of all patients, 22.8% had diabetes and 13% had hypertension. The type of surgery was caesarean section in 85.9%, laparatomy 8.7% and cystectomy/aforectomy in 5.4% and 18.5% of patients had a history of previous surgery. Conclusions: Due to the high rate of comorbidities and predisposing factors in patients with SSI, control of these factors can play an important role in preventing infection.